Reinforcing Corporate Accountability in Indonesian Environmental Law: A Dialectical Examination of Strict Liability and Criminal Sanctions - Andreas Tedy Mulyono; Carla Xelena Antunez; Rachel Nakeisha Darmadji; Zefanya Queenta Mangundihardjo; Safira Fadhilla Gunawan (Law Review, 2024)
Corporate accountability in Indonesia's environmental law still faces fundamental challenges, especially in the aspect of applying criminal sanctions against legal entities that commit environmental pollution or destruction. In practice, law enforcement relies more on administrative approaches or civil lawsuits, which often do not provide a deterrent effect and tend to be inadequate in responding to the complexity of environmental damage caused by corporations. This research aims to fill this gap by critically examining how the principle of strict liability can be integrated with the criminal sanction mechanism in national environmental law. With a normative juridical approach and supported by relevant case studies, this study shows that the synergy between the two approaches is able to form a more accountable, effective, and responsive accountability framework to the principles of sustainable development. The results of the analysis recommend the need for a holistic environmental law enforcement model, which not only emphasizes the repressive aspect, but also encourages structural improvements in corporate supervision and active public involvement in overseeing environmental law enforcement in Indonesia.